2018
DOI: 10.3390/ijms19103048
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Circulating MicroRNA Biomarkers in the Acute Pancreatic Injury Dog Model

Abstract: This study aimed to evaluate the usefulness of four microRNAs (miRNAs) in an acute pancreatic injury dog model. Acute pancreatitis was induced by infusion of cerulein for 2 h (7.5 μg/kg/h). The levels of well-known miRNAs, microRNA-216a (miR-216a) and microRNA-375 (miR-375), and new candidates microRNA-551b (miR-551b), and microRNA-7 (miR-7), were measured at 0, 0.5, 1, 2, 6, 12, and 24 h with serum amylase and lipase, and histopathological examination was performed. Among the four miRNAs, miR-216a and miR-375… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 26 publications
2
29
2
Order By: Relevance
“…Lee Hb et al have shown that miR-216a and miR-375 could predict the degree of pancreatic injury in dog model [11].Furthermore, some studies focused on serum miRNAs profiles of SAP patients with a specific organ failure [12,13]. Notably, the miRNAs profile in the present study was quite different from those reported by others [6,[9][10][11][12][13]. One possible reason is that the classifications of enrolled patients were different.…”
Section: Discussioncontrasting
confidence: 76%
See 1 more Smart Citation
“…Lee Hb et al have shown that miR-216a and miR-375 could predict the degree of pancreatic injury in dog model [11].Furthermore, some studies focused on serum miRNAs profiles of SAP patients with a specific organ failure [12,13]. Notably, the miRNAs profile in the present study was quite different from those reported by others [6,[9][10][11][12][13]. One possible reason is that the classifications of enrolled patients were different.…”
Section: Discussioncontrasting
confidence: 76%
“…An overexpression of miR-155 has been reported to be correlated with SAP [9], but it was also demonstrated to be inversely correlated with SAP in another study [10]. Lee Hb et al have shown that miR-216a and miR-375 could predict the degree of pancreatic injury in dog model [11].Furthermore, some studies focused on serum miRNAs profiles of SAP patients with a specific organ failure [12,13]. Notably, the miRNAs profile in the present study was quite different from those reported by others [6,[9][10][11][12][13].…”
Section: Discussionmentioning
confidence: 93%
“…These results indicate that miR-132 might function as a good biomarker to assess distress in gastrointestinal animal models, whereas miR-375, miR-30b and miR-203 might be biomarkers indicating disease-specific pathophysiological processes. For example, miR-375 was specifically induced during pancreatitis and this miRNA is known to be upregulated in patients and animals bearing chronic pancreatitis and might, therefore, reflect the degree of the pancreatic injury [31][32][33][34] . After BDL miR-375 expression was significantly downregulated.…”
Section: Discussionmentioning
confidence: 99%
“…Exogenous reference genes (Kong et al, 2010) miR-216a, miR-216b, and miR-375 Up SD rats L-arg Plasma Exogenous reference genes (Endo et al, 2013) miR-375, miR-217, miR-148a, and miR-122 (Lee et al, 2018) miR-216a and miR-217 Up C57BL6 mice and SD rats Caerulein, L-arg, or ligation of pancreatic duct Serum U6 (Goodwin et al, 2014) miR-216a and miR-217 Up C57BL6 mice and SD rats Caerulein or cyanohydroxybutene Serum Not mentioned (Wang et al, 2017) miR-216a, miR-216a, miR-375, and miR-217 Up SD rats Caerulein Serum Exogenous reference genes (Calvano et al, 2016) Abbreviations: AP, acute pancreatitis; miRNAs/miR, microRNAs. YANG ET AL.…”
Section: Plasmamentioning
confidence: 99%